Formation of professional competence of ecologists in professional training in higher agricultural educational establishments - RYBALKO, Yuliia (Journal of Education, Technology and Computer Science, 2013)
The paper identified and justified pedagogical conditions of professional competence of environmental, criterions and levels of professional competence of environmental, clarified the specific environmental professional training, professional environmental education in higher agricultural education, impro